2022
DOI: 10.3390/jcm11236976
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Endarterectomy for Chronic Thromboembolic Pulmonary Hypertension: A Systematic Review of the Most Updated Literature

Abstract: Pulmonary endarterectomy (PEA) is the treatment of choice in case of chronic thromboembolic pulmonary hypertension (CTEPH). PEA is performed by an increasing number of surgeons; however, the reported outcomes are limited to a few registries or to individual centers’ experiences. This systematic review focuses on pre-operative evaluation, intra-operative procedure and post-operative results in patients submitted to PEA for CTEPH. The literature included was searched using a formal strategy, combining the terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…TAPSE although the mean PVR (646 ± 454 dyn.s.cm −5 ) was not severely increased in our study. In a recent systematic review, the reported values of pre-PEA PVR ranged between 552 and 1536 dyn.s.cm −5 [24]. Several studies have shown that high pre-operative PVR values are associated with an increased mortality, with a 3 times higher in-hospital mortality in patients with pre-operative PVR > 1200 dyn.s.cm −5 [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…TAPSE although the mean PVR (646 ± 454 dyn.s.cm −5 ) was not severely increased in our study. In a recent systematic review, the reported values of pre-PEA PVR ranged between 552 and 1536 dyn.s.cm −5 [24]. Several studies have shown that high pre-operative PVR values are associated with an increased mortality, with a 3 times higher in-hospital mortality in patients with pre-operative PVR > 1200 dyn.s.cm −5 [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of PVR and PAP can worsen the outcome of PEA [ 7 ], and it is critical to minimize the increases in PAP and PVR. Anesthetic management is also required to ensure that the right heart is not stressed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of PH targeted medications as a bridging therapy before PEA to optimize hemodynamics may positively impact perioperative outcomes. However, controversy exists regarding the utilization of targeted therapies before PEA ( 8 ). Pilot studies with bosentan or prostacyclin demonstrated improved pre-PEA hemodynamics but no significant difference post-PEA compared to controls ( 9 - 11 ).…”
Section: Introductionmentioning
confidence: 99%